GAMBARAN PELAKSANAAN VAP BUNDLE (VAPb) PADA PASIEN YANG TERPASANG VENTILATOR - Nila Sari; Hellena Deli; Agrina Agrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Patients intubated and using ventilators for a long time are at risk of developing a nosocomial infection called Ventilator Associated Pneumonia (VAP). VAP events in the ICU can be minimized by the action procedure, VAP Bundle (VAPb). This study aims to describe the implementation of VAP Bundle (VAPb) in patients who have ventilators in the ICU. The research design used quantitative descriptive and the study sample was patients who were newly installed ETT / Intubation with mechanical ventilation within 1x24 hours, totaling 33 respondents were taken based on inclusion criteria with purposive sampling technique. Data collection tools in the form of VAPb observation sheets that have been modified and validated, data analysis is univariate analysis. The study was conducted by observing each VAPb applied by nurses to newly intubated patients and using a ventilator. The results of the study of the majority of respondents were 33.3% of late adulthood, male sex 60.5%, diagnosis of surgical disease 69.7%. Through univariate analysis, out of 33 respondents the percentage picture of hand hygiene by nurses, patient's oral hygiene and management of oroparyngeal and tracheal secretions was 100%. The percentage picture for setting the position of the patient's head is 72.8%. Of the 33 respondents who were supported, respondents agreed to document nursing in awakening patients every day in making integration reports (100%).The results showed that overall the implementation of VAPb in patients with ventilators not yet in accordance with predetermined VAPb, was due to the diagnosis and specific conditions of patients who restricted the administration of medicamentos and non-medicamentos. Suggestion: even though the administration of medicamentosa is not given related to the diagnosis and condition of the patient, documentation of nursing is still carried out. Keywords: Implementation of VAPb, VAPb, VAP